LOCAL ADAPTATION WHEN COMPETITION DEPENDS ON PHENOTYPIC SIMILARITY - Burgess, Scott C.; Waples, Robin S.; Baskett, Marissa L. (Evolution, 2013)
Recent work incorporating demographic–genetic interactions indicates the importance of population size, gene flow, and selection in influencing local adaptation. This work typically assumes that density-dependent survival affects individuals equally, but individuals in natural population rarely compete equally. Among-individual differences in resource use generate stronger competition between more similar phenotypes (frequency-dependent competition) but it remains unclear how this additional form of selection changes the interactions between population size, gene flow, and local stabilizing selection. Here, we integrate migration–selection dynamics with frequency-dependent competition. We developed a coupled demographic-quantitative genetic model consisting of two patches connected by dispersal and subject to local stabilizing selection and competition. Our model shows that frequency-dependent competition slightly increases local adaptation, greatly increases genetic variance within patches, and reduces the amount that migration depresses population size, despite the increased genetic variance load. The effects of frequency-dependence depend on the strength of divergent selection, trait heritability, and when mortality occurs in the life cycle in relation to migration and reproduction. Essentially, frequency-dependent competition reduces the density-dependent interactions between migrants and residents, the extent to which depends on how different and common immigrants are compared to residents. Our results add new dynamics that illustrate how competition can alter the effects of gene flow and divergent selection on local adaptation and population carrying capacities.